Dietary Diversity and Associated Factors among Children Aged 6-59 Months in Ethiopia: Analysis of Ethiopian Demographic and Health Survey 2016 (EDHS 2016) - Ataklti Gebretsadik Woldegebriel; Abraham Aregay Desta; Gebremedhin Gebreegziabiher; Asfawosen Aregay Berhe; Kiros Fenta Ajemu; Tewolde Wubayehu Woldearegay (Hindawi Limited, 2020)
Background. Dietary diversity is one of the key elements of diet quality. Even though different measures were taken to increase dietary diversity feeding practice in Ethiopia, the problem still remains high. Therefore, this study was done to identify determinants of inadequate minimum dietary practice among children aged 6-59 months in Ethiopia. Method. Secondary analysis of the data from the 2016 Ethiopian Demographic and Health Survey was done on a weighted sample of 5161 children aged 6-59 months. Data analysis was done using STATA v.14. Variables with P value < 0.05 in the bivariable analysis were candidates for the multivariable analysis to identify independent determinants of dietary diversity. Odds ratios (OR) were calculated at 95% confidence interval (CI). Results. A total of 5161 children aged 6 to 59 months were enrolled in the study. Only 8.5% of the children had the recommended minimum dietary diversity. Mother's education (adjusted odds ratio AOR=2.51 (1.65, 3.83)), mothers currently working (adjusted odds ratio AOR=1.83 (1.47, 2.29)), mother's wealth index (adjusted odds ratio AOR=4.75 (3.31, 6.81)), age of a child (adjusted odds ratio AOR=1.72 (1.24, 2.39)), and number of under-five children (adjusted odds ratio AOR=1.49 (1.12, 2.00)) were significantly associated with the minimum dietary diversity. Conclusion. The minimum dietary diversity was not achieved by most children 6-59 months of age in Ethiopia. Ensuring large-scale interventions that focus on the identified factors should be considered by concerned bodies to improve the dietary diversity practice.